Unsettled: Job Insecurity Reduces Home-Ownership - Anthony Lepinteur; Andrew E. Clark; Conchita D'Ambrosio (Institute of Labor Economics (IZA), 2024)
We here evaluate the link between job insecurity and one of the most-important decisions that individuals take: homeownership. The 1999 rise in the French Delalande tax on firms that laid off older workers produced an unexpected exogenous rise in job insecurity for younger workers. A difference-in-differences analysis of panel data from the European Community Household Panel shows that this greater job insecurity significantly reduced the probability of becoming a homeowner. This drop seems more attributable to individual preferences rather than greater capital constraints, consistent with individuals reducing their exposure to long-term financial commitments in more-uncertain environments.
Keywords: I38; J18; R21; 330; homeownership; job insecurity; employment protection; difference-in-differences